Hypoalbuminemia in critically sick children - Golhar, Sandeep T.; Agrawal, Hina; Chauhan, Urmila M.; Madhura, Abhishek (International Journal of Contemporary Pediatrics, 2019)
Background: Hypoalbuminemia at admission is a common finding in patients admitted to the Paediatric Intensive Care Unit (PICU) and may predict morbidity and mortality. Methods: Patients of age more than 1 year and less than 12 years diagnosed with hypoalbuminemia on the grounds of the inclusion criteria who were admitted in the Paediatric Intensive Care Unit (PICU) were enrolled in the study as ‘cases’ and patients with normal levels of serum albumin and otherwise similar characteristics to cases were included in the study as ‘controls’. Detailed clinical examination and required investigations were done. Above collected information was utilized to select two groups for the study i.e., those with hypoalbuminemia and others with no hypoalbuminemia. Both these groups were further followed up till discharge or death and the outcome in terms of morbidity and mortality was noted. Results: Incidences of MODS and degree of severity of illness as judged by PRISM III score in cases and control showed that, a lower serum albumin concentration correlated well with higher rates of complications such as ventilator dependence and development of new infections leading longer stay in the critical care unit. The mean length of PICU stay in cases group was statistically longer than in the control group. Although we did not observe a difference in fatal outcome in patients managed with either Human Albumin or Fresh Frozen Plasma compared to those managed conservatively in this study, we did observe a decreased mean length of PICU stay and rate of complications in the patients treated with either Human Albumin or Fresh Frozen Plasma, thus achieving a faster rate of recovery with lesser rate of complications and thus alleviating the morbidity, though still not being able to affect the overall mortality. Conclusions: Hypoalbuminemia at admission was a predictive factor of poor outcome in critically ill children. It is associated with a higher mortality, a longer length of stay in the PICU, as well as longer ventilator use.